Three new species of the genus Alloteratura Hebard, 1922 (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from China - Xin, Yarui; Shi, Fuming (Zootaxa, 2019)
This paper describes three new species of the genus Alloteratura Hebard, 1922 from China, i.e. Alloteratura (Alloteratura) sagittala sp. nov., Alloteratura (Alloteratura) flabellata sp. nov., Alloteratura (Meconemopsis) pentadactyla sp. nov., and provides characteristic photographs.